Tax Policy Options for a United Germany. (IMF Working Papers; Working Paper ;, 1990)
A central requirement in the rapid movement of German Democratic Republic (GDR) toward a market economy is the introduction of a market-oriented tax system. The paper highlights the main features of the traditional socialist tax structure of the GDR and the current tax structure of the Federal Republic of Germany (FRG). Arguments for an adequate short-term tax reform in the GDR are developed in two scenarios, contrasting the approach of taking over the FRG tax system (adoption scenario) and an autonomous tax reform in the GDR (reform scenario). Both scenarios recommend a flexible adjustment approach which anticipates the medium-term development of the German tax system pursuant to domestic reform requirements, international tax harmonization and fiscal federalism.